PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP PROFESIONALISME GURU SMK BISMEN DI KOTA TEGAL - Habibi, Beni (Dinamika Pendidikan, 2015)
The teacher professionalism reflects the teachers ability and performance in carrying out the duties to achieve education goals. In fact, there are many factors which influence the teacher professionalism. The objective of the study is to analyze the influence oÂ Â Â Â Â Â  f the rincipal`s managerial competence, work motivation, and those Â both variables toward teacher professionalism. It was a non-experimental quantitative approach. The population of the study was 172 teachers at Business and Management Vocational High Schools at Tegal city. The samples were taken by Krejcei table to get 114 teachers as the samples. Data were collected by questionnaire.Â  The results of the research showed that the principalâs managerial competence was good and significant, the influence of work motivation toward teacher professionalism was in good and significant category. Then, the influence of those both variables toward teacher professionalism was up to 47.8%. The regression analysis showed that: there was a positive and significant influence of the principalâs managerial competence toward teacher professionalism for 17.7%, work motivation gave positive and significant influence on teacher professionalism with the coefficient of determination was 46.8%. Furthermore; the results of multiple regression analysis showed that the influence of both variables simultaneously influenced teacher professionalism with the coefficient of determination was 47.8%.